(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The main objective of this study is to design a synthetic vaccine from the binder of sperm-1 (BSP1). Materials and Methods: This study was carried out using bioinformatics-related techniques. BSP-1 has been chosen as one of the biomarkers of a ruminant’s male fertility. We hypothesize that the BSP1 synthetic vaccines, which contain T-cell epitopes, can produce antibodies more effectively for the development of a sperm fertility detection kit. A sequence of BSP-1 peptides A0A0K1YXR5 from Bubalus bubalis (Domestic water buffalo) origin has been decided to be used to develop the peptide vaccine. Results: In this study, we succeeded in making synthetic vaccines from BSP-1 with a peptide sequence of LPEDSVPDEERVFPFTYRNRKHF. The three-dimensional theoretical prediction analysis of the peptide binding pattern to its ligand, as well as the molecular docking, has also been revealed. Conclusions: A synthetic vaccine from the BSP-1 has been developed in this study with the amino acid sequence LPEDSVPDEERVFPFTYRNRKHF, which is buffer-soluble, and the three-dimensional theoretical prediction analysis of the peptide binding pattern of BSP-1 to its ligand, as well as molecular docking, has also been revealed. J. Adv. Vet. Anim. Res., 9(1): 122–127, March 2022 http://doi.org/10.5455/javar.2022.i576